2002
DOI: 10.1051/ata/2002040
|View full text |Cite
|
Sign up to set email alerts
|

Les marqueurs biologiques de la consommation d'alcool

Abstract: RÉSUMÉ Les problèmes liés à la consommation d'alcool sont parmi les plus importants en addictologie, et constituent un problè-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These transaminases, together with gamma-glutamyl transferase, glycan-de cient transferrin, mean corpuscular volume, and a new parameter, γ-CDT are the different biological markers of alcoholization [3] Elevated transaminases are not common in drinkers except for liver disease [4]. Previous studies in alcoholic patients have demonstrated several liver-derived biomarkers associated with excessive ethanol consumption and alcoholic liver disease [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These transaminases, together with gamma-glutamyl transferase, glycan-de cient transferrin, mean corpuscular volume, and a new parameter, γ-CDT are the different biological markers of alcoholization [3] Elevated transaminases are not common in drinkers except for liver disease [4]. Previous studies in alcoholic patients have demonstrated several liver-derived biomarkers associated with excessive ethanol consumption and alcoholic liver disease [5,6,7].…”
Section: Introductionmentioning
confidence: 99%